2010
DOI: 10.3109/15412555.2010.528087
|View full text |Cite
|
Sign up to set email alerts
|

Lung Hyperinflation and Its Reversibility in Patients with Airway Obstruction of Varying Severity

Abstract: The natural history of lung hyperinflation in patients with airway obstruction is unknown. In particular, little information exists about the extent of air trapping and its reversibility to bronchodilator therapy in those with mild airway obstruction. We completed a retrospective analysis of data from individuals with airway obstruction who attended our pulmonary function laboratory and had plethysmographic lung volume measurements pre-and post-bronchodilator (salbutamol). COPD was likely the predominant diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
90
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(105 citation statements)
references
References 35 publications
10
90
1
4
Order By: Relevance
“…In addition to serving as an index for survival, IC has also emerged as a useful tool for assessing changes in gas trapping for various therapies. For example, Van Noord and co-workers 37 39 Notably, they found an increased RV in mild, moderate, and severe obstruction. They also observed that the largest change in percent of predicted following bronchodilator and the frequency of a positive response was greatest for RV ( Fig.…”
Section: Do Lung Volumes Tell Us Anything Meaningfulmentioning
confidence: 99%
“…In addition to serving as an index for survival, IC has also emerged as a useful tool for assessing changes in gas trapping for various therapies. For example, Van Noord and co-workers 37 39 Notably, they found an increased RV in mild, moderate, and severe obstruction. They also observed that the largest change in percent of predicted following bronchodilator and the frequency of a positive response was greatest for RV ( Fig.…”
Section: Do Lung Volumes Tell Us Anything Meaningfulmentioning
confidence: 99%
“…The natural evolution of hyperinflation in patients with COPD is unclear, but data suggest that it can present even in patients with mild COPD, and increases exponentially as disease severity worsens [37]. On a related note, there is increasing evidence supporting the correlation of CT-derived emphysema assessment with physiological markers of hyperinflation (most commonly RV, RV/TLC and resting IC and FRC) [38][39][40][41][42].…”
Section: Characteristics Of the Eh Phenotype: Hyperinflationmentioning
confidence: 99%
“…Some also have a positive effect on exacerbation rates, healthcare utilisation and, possibly, mortality [93,94,96,[113][114][115][116][117][118]. One study highlighted the fact that bronchodilators predominantly exert their effects on measures of resting hyperinflation, even when little or no change in FEV1 is observed [37]. In addition, a study investigating the predictors of improvement in exercise tolerance following treatment of short-acting bronchodilator (ipratropium bromide, three times a day for a 3-week period) found that an increased resting IC was the best predictor of change in endurance time following bronchodilation, and that the change in FEV1 was not [119].…”
Section: Treatmentmentioning
confidence: 99%
“…Lung-volume measurements are used infrequently but may show significant changes, particularly in the presence of hyperinflation or air trapping. 23 Airway resistance and conductance, measured by body plethysmography, often improve significantly even though FEV 1 does not. Because of the variability in airway resistance and conductance in healthy subjects, improvements of 40 -50% are necessary to conclude that reversibility is present.…”
Section: Bronchodilator Testingmentioning
confidence: 99%